Prototipe Mesin Penghitung Potongan Botol Plastik Kemasan 1,5 Liter - Yudhi Agussationo; Mahmud Idris; Andri Arianto (Jurnal Elektronika, Listrik, dan Teknologi Informasi Terapan, 2022)
Especially ornamental fish farmers. This bottle a function as a medium for freshwater ornamental fish containers. hardware bottle-cutting tool to be controlled using programming software using an Arduino microcontroller with the help of an infrared sensor. This Arduino microcontroller will make it easier for users to calculate the bottles that have been cut and the cost of cutting bottles that will be displayed on the 20 x 4 LCD without having to calculate manually which will take more time. In addition to the many features obtained by the owner/user, they can also benefit from selling bottles that will be traded to freshwater ornamental fish farmers. With this innovation, besides simplifying human tasks, can also educate the user community so that they can innovate for the development of the ornamental fishery sector.